Chemical Composition and Antimicrobial Potential of Palm Leaf Extracts from Babaçu (Attalea speciosa), Buriti (Mauritia flexuosa), and Macaúba (Acrocomia aculeata) - Adriana Idalina Torcato de Oliveira; Talal Suleiman Mahmoud; Guilherme Nobre L. do Nascimento; Juliana Fonseca Moreira da Silva; Raphael Sanzio Pimenta; Paula Benevides de Morais (The Scientific World Journal)
Babaçu (A. speciosa), Buriti (M. flexuosa), and Macaúba (A. aculeata) are palm trees typical of the ecotone area between Cerrado and the Amazon rainforest. The purpose of this study was to evaluate the antimicrobial potential of the extracts prepared from the leaves of those palms as well as determine their chemical compositions. The ethanol extracts were prepared in a Soxhlet apparatus and tested by disk diffusion and agar dilution technique against Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, Pseudomonas aeruginosa, Candida albicans, and Candida parapsilosis. However, there was no significant activity at concentrations of 25, 50, and 100 mg·Ml−1. Moreover, the phytochemical analysis revealed the presence of tannins, flavonoids, catechins, steroids, triterpenes, and saponins. Gas chromatography (GC/MS) analysis also identified organic acids, such as capric (decanoic) acid, lauric (dodecanoic) acid, myristic (tetradecanoic) acid, phthalic (1,2-benzenedicarboxylic) acid, palmitic (hexadecanoic) acid, stearic (octadecanoic) acid, linoleic (9,12-octadecadienoic) acid (omega-6), linolenic (octadecatrienoic) acid (omega-3), and the terpenes citronellol and phytol. Based on the chemical composition in the palm leaf extracts, the palms have the potential to be useful in the food, cosmetic, and pharmaceutical industries.